1990
DOI: 10.1111/j.1432-1033.1990.tb19273.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nucleotides, actin and temperature on thermolysin digestion of myosin subfragment‐1

Abstract: Myosin subfragment-1 from rabbit skeletal muscle was digested by thermolysin at 25", 12" and 0°C. Thermolysin cleaves subfragment-1 heavy chain into two stable fragments, 28 kDa and 70 kDa, aligned in this order from the N-terminus [Applegate, D. & Reisler, E. (1983) Proc. Nut1 Acad. Sci. U S A 80, 7109-71121. The rate of digestion at 25°C was significantly increased in the presence of MgATP and somewhat less in the presence of MgADP, or magnesium pyrophosphate. This activating effect of the nucleotides was de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 36 publications
(13 reference statements)
1
3
0
Order By: Relevance
“…We favour the second possibility because Lys553 is accessible also in the presence of actin as shown by the lack of actin effect on the nitromethane quenching of the fluorescence of the Lys553‐bound FH moiety and by the finding that the binding of FH‐S1 to F‐actin is not impeded [16]. Thus the present results support the earlier findings [14,15,28,29] that actin affects the conformation of myosin, which should be taken into account in describing the structural changes taking place during the cross‐bridge cycle.…”
Section: Discussionsupporting
confidence: 90%
“…We favour the second possibility because Lys553 is accessible also in the presence of actin as shown by the lack of actin effect on the nitromethane quenching of the fluorescence of the Lys553‐bound FH moiety and by the finding that the binding of FH‐S1 to F‐actin is not impeded [16]. Thus the present results support the earlier findings [14,15,28,29] that actin affects the conformation of myosin, which should be taken into account in describing the structural changes taking place during the cross‐bridge cycle.…”
Section: Discussionsupporting
confidence: 90%
“…Thermolysin cleaves SI heavy chain at 26 kDa from the N-terminus (Applegate & Reisler, 1983) after Glu-208 or Ala-209 (Yamamoto, 1989b). This cleavage is enhanced by nucleotides and inhibited by actin (Applegate & Reisler, 1983Muhlrad & Chaussepied, 1990), indicating that communication exists between this site and both the nucleotideand actin-binding sites. We found that methylation does not affect the thermolysin cut in the absence of nucleotides and actin, except for a further degradation of the 26 kDa product.…”
Section: Resultsmentioning
confidence: 95%
“…The former would suggest that the epitope is near to the myosin-actin interface, while the latter would indicate that there is communication between the actin and the antibody-binding sites on the 50 kDa domain. The first possibility is supported by the actin inhibition of the papain and the thermolysin cleavage at the 27 kDa/50 kDa junction of S-1 (Applegate & Reisler, 1983;Muhlrad & Chaussepied, 1989) while the second is supported by cross-linking studies (Morner et al, 1981;Sutoh, 1983) which point to the involvement of the C-terminal and not the N-terminal region of the 50 kDa fragment in the myosin-actin interface.…”
Section: Discussionmentioning
confidence: 96%